External Factors Affecting Da'if Hadith Validity: A Study on 'The Talqah of the Ummah in Al-Qabul' and Water Purity Changes - Abdurrohman, Irwan; Mubarok, Muhamad Raihan Syahrul (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to analyze the concept of the validity of